Prophet of the Six Senses? On the Sensuality of Czesław Miłosz’s Christian Imaginarium - Banowska, Lidia (2024)
This article discusses the sensual dimension of Czesław Miłosz’s work, the hidden unity of which lies in the Christian character of the poetic imaginarium, encompassing the vision of the world, man and God in their entirety. This imaginarium, based on the concreteness of sensual imagery, remains an important aid for Miłosz in approaching the mysteries of faith, enabling him to transcend the abstractness of rational inquiry. Sensuality is both an expression of Miłosz’s writing personality and the rationale for his worldview. For the poet, the sensuality of the world is an expression of both the reality of being and the beauty of creation, and thus a trace of the hand of God. With the passage of time, from an interest in the sensual beauty of the temporal world, treated as a sign of the eternal world, the poet arrives at a concentration of attention on the perception of man, who through divinisation can become a sign of God and an embodied foreshadowing of heaven. Images of a reality that “eye hath not seen nor ear has heard”, defined by sensual visions of a “second space”, images of light or moments of epiphany, become in the works of Miłosz, this “prophet of the six senses”, an expression of another sense, the “sense of faith”, enabling humans to experience a “sense of eternity”.
Keywords: Miłosz, Czesław